The Clinicopathologic Evaluation of Eosinophilic Cholecystitis: A Retrospective Observational Study in a Tertiary Care Center - Erdogan-Durmus, Senay; Balta, Hilal; Ozmen, Sevilay; Calik, Ilknur; Can, Yusuf; Kurt, Ali (Annals of Pathology and Laboratory Medicine, 2021)
Background: Eosinophilic cholecystitis (EC) is a rare form of cholecystitis that is diagnosed histopathologically. The aim of this study to evaluate the patient demographic features, laboratory findings and histopathologic characteristics of EC. The aim of this study to evaluate the patient demographic features, laboratory findings and histopathologic characteristics of EC. Design and setting: Retrospective observational study conducted in Erzurum, Turkey. Methods: Between June 2014 and June 2017 3,178 cholecystectomy specimens were reviewed retrospectively. Nineteen EC cases were included to the study. Parameters such as sex, age, clinical information, laboratory findings were obtained from information system of hospital. And the data of EC group were compared with a control group of 50 non-specific chronic cholecystitis patients (CC). Result: Out of 3,178 cholecystectomy specimens, 19 cases were diagnosed as EC (0.59%). Patients’ age ranged from 22-84 years and female to male ratio was 1.7:1. The average eosinophil count was 139.7 U/L in EC group. 11.7% of EC group had high level for eosinophils. In the EC group there were statistical significances between high eosinophil percentages and aspartate transaminase (AST), alkaline phosphatase (ALP) values (P<0.05, P<0.05). The EC group eosinophil levels were slightly higher than CC. Histopathologically, dense, severe infiltrates composed of eosinophils were seen. Conclusion: EC is a rare entity that can only diagnosed by histopathology. There were certain high levels in liver function tests and eosinophils in correlation with non-specific cholecystitis. Although the presentation may be similar to non-specific cholecystitis, if a postoperative histopathological diagnosis of EC is made, then the patient must be investigated thoroughly to rule out other associated disease conditions.